2015
DOI: 10.1152/ajplung.00213.2014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized glutathione (GSSG) inhibits epithelial sodium channel activity in primary alveolar epithelial cells

Abstract: Downs CA, Kreiner L, Zhao XM, Trac P, Johnson NM, Hansen JM, Brown LA, Helms MN. Oxidized glutathione (GSSG) inhibits epithelial sodium channel activity in primary alveolar epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
(63 reference statements)
0
17
0
Order By: Relevance
“…Reactive oxidants have also been shown to alter ENaC activity by either posttranslational modifications (such as oxidation, nitration, nitrosylation, and glutathionylation of critical residues) or through activation of signal transduction pathways (96). Furthermore, oxidized glutathione has been shown to inhibit ENaC activity in primary alveolar epithelial cells (18,33). Lazrak et al (54) measured the induction of reactive oxygen species (ROS) by M2 overexpression.…”
Section: Inhibition Of Enac and Cftr By Influenza Virus M2 Proteinmentioning
confidence: 99%
“…Reactive oxidants have also been shown to alter ENaC activity by either posttranslational modifications (such as oxidation, nitration, nitrosylation, and glutathionylation of critical residues) or through activation of signal transduction pathways (96). Furthermore, oxidized glutathione has been shown to inhibit ENaC activity in primary alveolar epithelial cells (18,33). Lazrak et al (54) measured the induction of reactive oxygen species (ROS) by M2 overexpression.…”
Section: Inhibition Of Enac and Cftr By Influenza Virus M2 Proteinmentioning
confidence: 99%
“…We have previously shown that ENaC activity is dependent on levels of ROS, particularly superoxide (25)(26)(27)(28). We felt that our observed results were due to excess mitochondrial ROS production, but TEMPOL reduces ROS throughout the cell.…”
Section: The Role Of Rosmentioning
confidence: 78%
“…In resting cells, no more that 50 μmol L −1 of GSSG could be detected and thus experimental settings described in Ref. clearly represent conditions of severe oxidative stress. On the other hand, application of an antioxidant N‐acetylcystein (NAC) inhibited amiloride‐sensitive current in nasal epithelial cells .…”
Section: Discussionmentioning
confidence: 98%
“…It should be also noted that millimolar concentrations of H 2 O 2 used in those studies are clearly out of the physiological limits of DUOX‐mediated H 2 O 2 production. In this respect, it is interesting to mention that application of 400 μmol L −1 oxidized glutathione (GSSG) directly to primary rat epithelial Type II cells induced decrease in ENaC open probability . In resting cells, no more that 50 μmol L −1 of GSSG could be detected and thus experimental settings described in Ref.…”
Section: Discussionmentioning
confidence: 99%